THE EFFECT OF MEDIA PROVISION ON KNOWLEDGE ABOUT “ISI PIRINGKU” IN ADOLESCENTS - Fajri, Andhika Kusuma; Kurniasari, Ratih (HEARTY, 2025)
Due to rapid globalization, poor diet and lifestyle, especially in adolescents, can greatly affect their health. Ignorance about nutrition in adolescents can lead to irregularities in nutrient intake and energy expenditure, which will likely lead to undernutrition and overnutrition problems. This study aims to determine the effect of media provision on students of SMPN 2 East Karawang. The research method used quasy experiment method with purposive sampling technique. Knowledge was assessed using a questionnaire then descriptive analysis was carried out using SPSS if the data was normally distributed using the paired sample test if the data was not normally distributed then using the Wilcoxon test. The results of the study showed that there was an effect of media provision on knowledge about “Isi Piringku” with a value of p <0.05. The conclusion of this study shows that there is an effect of media provision on knowledge about “Isi Piringku” in students of SMPN 2 East Karawang.